KELAYAKAN INFOGRAFIS PETA SHELTER UNP SEBAGAI MITIGASI BENCANA GEMPA DAN TSUNAMI - Dwi Mutia Sari; Haris Satria; Eko Purnomo; Siti Aisyah (Narada : Jurnal Desain dan Seni, 2023)
The purpose of this study was to analyze the development process, feasibility and academic community response to the Universitas Negeri Padang (UNP) shelter map infographic as one of the media in earthquake and tsunami disaster mitigation. The method in this study uses the development research method or Research and Development (R&D), in order to produce certain products based on the stages so as to produce a feasible product. The validation test was carried out by design and media experts using validation sheets, then field trials on 20 students. The results showed that: 1) the feasibility of UNP shelter map infographics as one of the media in earthquake and tsunami disaster mitigation with the results of design and media expert validation with a very feasible category of 94.23%, 2) student responses to understanding UNP shelter map infographics as one of the media in earthquake and tsunami disaster mitigation obtained results of 91.66% which can be categorized as easy to understand as one of earthquake and tsunami disaster mitigation.